2022
DOI: 10.3758/s13428-022-01956-8
|View full text |Cite
|
Sign up to set email alerts
|

A spurious correlation between difference scores in evidence-accumulation model parameters

Abstract: Evidence-accumulation models are a useful tool for investigating the cognitive processes that give rise to behavioural data patterns in reaction times (RTs) and error rates. In their simplest form, evidence-accumulation models include three parameters: The average rate of evidence accumulation over time (drift rate) and the amount of evidence that needs to be accumulated before a response becomes selected (boundary) both characterise the response-selection process; a third parameter summarises all processes be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Even if researchers are not interested in NDT itself, not knowing when it should be constrained or not has consequences on other parameter estimates. For instance, it has recently been shown that estimates of between-condition differences in NDT and boundary separation (meant to capture caution) are negatively correlated (Grange & Schuch, 2021). This occurred in simulations when there were no real differences in either parameter.…”
Section: Non-decision Time In Decision Modelsmentioning
confidence: 99%
“…Even if researchers are not interested in NDT itself, not knowing when it should be constrained or not has consequences on other parameter estimates. For instance, it has recently been shown that estimates of between-condition differences in NDT and boundary separation (meant to capture caution) are negatively correlated (Grange & Schuch, 2021). This occurred in simulations when there were no real differences in either parameter.…”
Section: Non-decision Time In Decision Modelsmentioning
confidence: 99%
“…The situation looks different, though, when difference scores are computed between two conditions, as has been traditionally done when estimating effects of executive control (e.g., Miyake et al 2000;Stahl et al 2014). In fact, there is evidence that difference scores computed from diffusion model parameters are particularly spurious (Grange and Schuch 2022) which impedes testing their relations with correlates of interest. The lack of reliability stems from at least two sources.…”
Section: Psychometric Challengesmentioning
confidence: 99%
“…Such reliability issues may be less of a problem in experimental research, where sufficient data is available from all participants to derive reliable mean estimates for the experimental conditions. However, it can turn out to be a challenge when individual differences are concerned (Grange and Schuch 2022;Schmiedek et al 2007). One possible solution is to treat parameter estimates as error-prone indicators of latent parameter factors that can be modeled by means of structural equation modeling.…”
Section: Psychometric Challengesmentioning
confidence: 99%